Depression in the Wake of Cyberbullying: A Gender-Sensitive Study Among Indonesian Adolescents - Gelsie Theresa Prameswary Rasubala; Wahyuni Kristinawati (Universitas PGRI Yogyakarta, 2026)
This study aims to explore the relationship between cyberbullying victimization and depression in Indonesian adolescents aged 14–19 years with a quantitative correlational approach. The research sample consisted of 154 respondents, selected through incidental sampling, and data were collected using an online questionnaire. The instruments used are the Cyber-Victimization Scale (CYBVICS) to measure the level of cyberbullying victimization and the Beck Depression Inventory-II (BDI-II) to measure symptoms of depression. The results of the analysis showed that in adolescent boys, there was a significant positive relationship between cyberbullying victimization and depression, while in teenage girls, the relationship was not significant. Statistical tests also showed that the data distribution for depression variables was normally distributed, while for cyberbullying victimization was not. However, the relationships between variables are assumed to be linear. These findings provide important insights into the different psychological responses between genders to cyberbullying and its implications for prevention interventions and the management of adolescent mental health problems in the digital age. Keywords: cyberbullying, gender, adolescents